Modelling the potential importance of wildlife for rabies persistence in Machakos District, Kenya - Kitala, P.M.; Coleman, P.G.; McDermott, John J. (International Society for Veterinary Epidemiology and Economics, 2000)
The mechanisms by which the rabies virus persists in a host population are unclear. Mathematical models of rabies have difficulty in explaining how the rabies virus persists in the host population between epidemics. Simple deterministic models of rabies predict an unrealistically low number of infected hosts (i.e. fractions of infected hosts) between the first epidemic, following introduction of tile virus, and the second epidemic, after sufficient replenishment of susceptibles. It is in such inter-epidemic troughs, when the prevalence of the vine is at its lowest, that the chances of epidemic fadeout are greatest. Across East Africa, rabies is an important public health problem, and the domestic dog is regarded as the primary reservoir of disease and main vector of human rabies. Rabies cases in wildlife are said to represent spill-over infections which are not important in the long-term persistence of the virus. In Kenya, the rabies problem has been greatest in Machakos District where the disease has persisted, predominantly in domestic dogs although with regular wildlife cases, even when it was well controlled in the rest of the country". Here we investigate what contribution the infections in wildlife might play in the overall persistence of rabies in the domestic dog population of Machakos. We use simple deterministic models of rabies transmission in domestic dog and wild carnivore populations to examine the effects of inter-specific transmission (i.e. dog to wildlife and wildlife to dog) on the persistence of rabies between epidemic peaks.